2014
DOI: 10.1002/imhj.21465
|View full text |Cite
|
Sign up to set email alerts
|

Strong, Safe, and Secure: Negotiating Early Fathering and Military Service Across the Deployment Cycle

Abstract: Military fathers of young children often endure repeated separations from their children, and these may disrupt the early parent-child relationship. Postdeployment reunification also poses challenges; disruptions that have occurred must often be repaired in the context of heightened emotions on the part of each family member at a time when fathers are themselves readjusting to the routines and responsibilities of family life. The current study employed qualitative research with the central aim of informing a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Service members who have deployed have elevated rates of posttraumatic stress disorder (PTSD), with studies reporting 4 to 17% prevalence rates for U.S. Iraq War veterans (Richardson, Frueh, & Acierno, ), but substantially more may suffer from subclinical symptoms. For example, while most participants in a small study of military fathers who participated in a parenting support intervention did not meet cutoff criteria for a probable diagnosis of PTSD on a standard self‐report checklist, nearly half had subclinical, but elevated, levels of trauma symptoms (Dayton et al., ). Over half of spouses of service members report negative emotional reactions (anxiety, loneliness, sadness, worry) related to their partner's deployment separation (Wexler & McGrath, ).…”
Section: Psychological Impact Of Military Service On Parentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Service members who have deployed have elevated rates of posttraumatic stress disorder (PTSD), with studies reporting 4 to 17% prevalence rates for U.S. Iraq War veterans (Richardson, Frueh, & Acierno, ), but substantially more may suffer from subclinical symptoms. For example, while most participants in a small study of military fathers who participated in a parenting support intervention did not meet cutoff criteria for a probable diagnosis of PTSD on a standard self‐report checklist, nearly half had subclinical, but elevated, levels of trauma symptoms (Dayton et al., ). Over half of spouses of service members report negative emotional reactions (anxiety, loneliness, sadness, worry) related to their partner's deployment separation (Wexler & McGrath, ).…”
Section: Psychological Impact Of Military Service On Parentsmentioning
confidence: 99%
“…Adjustment back to home life and day‐to‐day parenting often involves co‐managing their children's emotions. Many service members have reported difficulty helping their children regulate their emotions, and note that their children's negative emotions can trigger difficult memories from their military and combat experiences (Dayton et al., ). Military parents have reported that they have difficulty reestablishing connections with their younger children upon reunification, nurturing and being emotionally available to their children, and managing their child's emotions (and staying calm themselves) when their child is upset (Walsh et al., ).…”
Section: Parenting In Military Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies reported the salaries of the service members, and these data also ranged widely across studies, even within military branch. For example, 66% of the Army National Guard fathers participating in the study by Dayton et al (2014) earned less than $50,000, and 50% were unemployed. In contrast, the median reported income of Army National Guard families participating in the study by Gewirtz et al (2014b) was $80,000.…”
Section: Child Behavioral Healthmentioning
confidence: 98%
“…Yogman and Garfield () explained that the level of involvement of physically absent or nonresident fathers with their children is influenced by several factors, including age, level of education, employment status, geographical distance, fathers' mental health status and social support. To date, research related to fathers' physical absences early in their infants' lives has focused either on fathers' experiences of separation from their hospitalized newborns/infants (Garten, Maass, Schmalisch, & Buhrer, ) or deployed military fathers (Dayton, Walsh, Muzik, Erwin, & Rosenblum, ; Schachman, ; Willerton, Schwarz, Wadsworth, & Oglesby, ). Garten et al () compared the frequency and duration of parental visits to neonatal intensive care unit (NICU) and found the frequency of parental visits declined significantly over time, while the duration of visits remained constant.…”
Section: Introductionmentioning
confidence: 99%